Antimicrobial Susceptibility and Virulence Surveillance of Campylobacter spp. Isolated From Patients in Two Tertiary Medical Centers in Taiwan - Ge, Mao-Cheng; Kuo, Shu-Fang; Chang, Shih-Cheng; Chien, Chun-Chih; You, Huey-Ling; Lu, Jang-Jih (Frontiers in Microbiology, 2019)
Campylobacter spp. may cause fever, vomiting, and diarrhea in humans. Antibiotic treatment is suggested for patients with severe Campylobacter infection. However, the interpretative criteria for antibiotic susceptibility are inconsistent between Clinical and Laboratory Standards Institute and European Committee on Antimicrobial Susceptibility Testing guidelines. To investigate the antibiotic susceptibility and prevalence of cytolethal distending toxin genes and to evaluate antibiotic susceptibility testing methods in the clinical laboratories of two tertiary medical centers in Taiwan. In total, 236 (165 and 71 isolates from northern and southern Taiwan, respectively) bacterial isolates were collected between 2001 and 2014. The disc diffusion and E-test methods were used to evaluate the antibiotic susceptibility, and broth dilution results were used as a reference. The virulence genes cdtA, cdtB, cdtC, and cdtE were detected through polymerase chain reaction. The sensitivity rates for erythromycin, ciprofloxacin, and tetracycline assessed using the broth dilution assay were 80.4%, 5.4%, and 3.4%, respectively. No significant differences were observed in the antibiotic susceptibility the isolates obtained from southern and northern Taiwan. However, some differences were observed between species. The susceptibility test for erythromycin (disc diffusion) showed that the isolates with small inhibition zone diameters (IZD ? 6 mm) were all resistant, and five isolates (4.0%) with large IZDs (>6 mm) were nonsensitive. The error rate of the disc diffusion method according to the CLSI M45-A3 guideline was 5.4% (8/148). The incompatibility rates between the E-test and broth dilution methods for erythromycin, ciprofloxacin, and tetracycline were 8.0%, 5.3%, and 1.3%, respectively. The positive rates of the genes cdtA and cdtC were considerably higher in C. jejuni than in C. coli. Erythromycin is recommended as the first choice of treatment for severe or invasive Campylobacter infection. The disc diffusion method is suitable for prescreening Campylobacter susceptibility by using the CLSI M45-A2 (resistant IZD ? 6 mm) and EUCAST (sensitive IZD ? 20 mm) criteria (low error rate of 3.4%). If antibiotic treatment fails or IZDs are between 6 and 20 mm, minimum inhibitory concentration testing by using the E-test method is highly recommended because the results of the E-test and broth dilution methods exhibit high agreement.